Nicotine preloading for smoking cessation: the Preloading RCT - Aveyard, Paul; Lindson, Nicola; Tearne, Sarah; Adams, Rachel; Ahmed, Khaled; Alekna, Rhona; Banting, Miriam; Healy, Mike; Khan, Shahnaz; Rai, Gurmail; Wood, Carmen; Anderson, Emma C; et al. (NIHR Health Technology Assessment Programme, 2018)
Background: Nicotine preloading means using nicotine replacement therapy prior to a quit date while smoking normally. The aim is to reduce the drive to smoke, thereby reducing cravings for smoking after quit day, which are the main cause of early relapse. A prior systematic review showed inconclusive and heterogeneous evidence that preloading was effective and little evidence of the mechanism of action, with no cost-effectiveness data.